Optimalisasi Model Praktik Keperawatan Primer di Ruang Elisabet Rumah Sakit Immanuel Bandung - Tiarmaida Sitio; Alexander Mela; Asep Suhendar; Sari Ratna Dewi (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
The Professional Nursing Practice Model (MPKP) serves as a framework for the provision of nursing care, facilitating professional nurses in exercising their autonomy in the planning, execution, and assessment of nursing interventions directed towards clients. This investigation was undertaken to evaluate the advancement of the primary nursing practice model within the inpatient Elizabeth Room of Immanuel Hospital. Employing a pre-experimental research design characterized by a one-group control framework, the study utilized a pre-test and post-test methodology within the same cohort. The findings of this research reveal a notable enhancement in knowledge following the application of the primary nursing practice model. Prior to the model's implementation, a majority of nurses achieved scores that predominantly fell within the moderate category, with only a limited number attaining the highest scores, as evidenced by four primary nurses who received a minimum score of 7 (70%). Subsequent to the model's implementation, the distribution of scores exhibited a more uniform pattern, with an increased number of nurses attaining optimal scores, including two nurses who reached the maximum score of 10 (100%), and the average evaluation following the introduction of the primary nursing practice model was calculated to be 92.43%. This improvement can be postulated as a consequence of the primary nursing practice model's approach, which underscores the significance of holistic care and individual accountability in the delivery of health services. In light of these findings, we advocate for the adoption of the primary nursing practice model in inpatient care settings, as it demonstrably contributes to the enhancement of patient quality and safety within nursing services in hospitals, thereby necessitating ongoing clinical leadership training for primary nurses, in conjunction with efforts to elevate the formal educational qualifications of nurses who currently possess diploma-level credentials.Assignment Method (MPKP)